Inside Back Cover: A Graphene Composite Material with Single Cobalt Active Sites: A Highly Efficient Counter Electrode for Dye‐Sensitized Solar Cells (Angew. Chem. Int. Ed. 23/2016). Issue 23 (29th April 2016) - Cui, Xiaoju; Xiao, Jianping; Wu, Yihui; Du, Peipei; Si, Rui; Yang, Huaixin; Tian, Huanfang; Li, Jianqi; Zhang, Wen‐Hua; Deng, Dehui; Bao, Xinhe
Abstract : The incorporation of single cobalt active sites within a graphene matrix leads to a composite material with superior activity and stability when used as a counter electrode for the interconversion of the redox couple I − /I3 − . In their Communication onpage 6708 ff., D. Deng, W.‐H. Zhang, and co‐workers further show that the use of this material as a counter electrode in a dye‐sensitized solar cell (DSSC) leads to a better power conversion efficiency than the use of a platinum counter electrode.